Obstacles And Challenges In Implementing Immunization In Coastal Communities - Achmad Hilal; Rahmat Pannyiwi (International Journal of Health Sciences, 2026)
Immunization is an effective promotive and preventive measure in preventing infectious diseases. However, immunization coverage in some coastal areas is still suboptimal. Geographical, social, and cultural conditions, as well as limited access to health services, are factors that influence immunization implementation. This study aims to identify obstacles and challenges to immunization implementation in coastal communities. This study used quantitative methods with a descriptive analytical design and a cross-sectional approach. Sectional. The research sample was mothers who have toddlers in coastal area X. Data were collected using questionnaires and analyzed univariately and bivariately. The results showed that the main obstacles to immunization implementation include access to health services, maternal knowledge, perceptions of immunization, and family support. The conclusion of this study is that the implementation of immunization in coastal communities still faces various obstacles that require integrated interventions.